Kirkpatrick Four-level Model Evaluation: An Evaluation Scale on the Preservice Teacher’s Internship Program - Dalimunthe, Muhammad Bukhori (Journal of Education Reseach and Evaluation, 2022)
Internship programs are organized depending on the program provider (school), so many students have a big difference in the internship experience. On the other hand, the campus has limitations in running the program, one of which is evaluating the achievement of the internship program. The purpose of this study is to build validity on the evaluation scale of the apprenticeship program for pre-service teachers using Kirkpatrick's four-level evaluation model. This type of research is quantitative with a confirmatory quantitative approach. The sample is 212 pre-service teachers. The methods used in collecting data are observation, tests, and questionnaires. Instruments used for test sheets and questionnaires. Data analysis used a confirmatory factor analysis (CFA) approach with the SmartPLS v3.0 application. The analysis results are that the four-level evaluation model meets construct validity and proves accurate validation on the internship program evaluation scale. In particular, the internship program evaluation scale effectively tracks program achievements at each level. The implication is that academic stakeholders on campus can use this evaluation scale as a measuring tool to experiment with the success of the internship program. In addition, they can review the achievements of pre-service teachers in implementing apprenticeship programs based on each level of the Kirkpatrick model.